Adjuvant therapy after resection of colorectal liver metastases: the predictive value of the MSKCC clinical risk score in the era of modern chemotherapy - Rahbari, Nuh Nabi; Reißfelder, Christoph; Schulze-Bergkamen, Henning; Jäger, Dirk; Büchler, Markus W.; Weitz, Jürgen; Koch, Moritz (BMC cancer, 2014)
Despite introduction of effective chemotherapy protocols, it has remained uncertain, if patients with colorectal cancer (CRC) liver metastases should receive adjuvant therapy. Clinical or molecular predictors may help to select patients at high risk for disease recurrence and death who obtain a survival advantage by adjuvant chemotherapy.
Gesehen am 05.08.2020